2023
DOI: 10.1039/d2ya00348a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and interactions of novel ether-functionalised morpholinium and piperidinium ionic liquids with lithium salts

Abstract: Investigation of the thermodynamic and transport properties of four novel ether-functionalised piperidinium and morpholinium ionic liquids with LiFSI and LiTFSI salts, and Li-ion coordination in ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…It is worth noting that both electrolytes exhibit relatively small fragility factor, D , consistent with the behaviour of liquids that form fragile glass structures. A comparison of the VFT parameters with other IL-salt electrolytes, 55,56 indicates that the pseudo activation energies ( B ) in both electrolytes are either in the same range or lower than the other electrolytes. A comparison of the T 0 values also shows that they are lower in comparison to some ILs reported in the literatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that both electrolytes exhibit relatively small fragility factor, D , consistent with the behaviour of liquids that form fragile glass structures. A comparison of the VFT parameters with other IL-salt electrolytes, 55,56 indicates that the pseudo activation energies ( B ) in both electrolytes are either in the same range or lower than the other electrolytes. A comparison of the T 0 values also shows that they are lower in comparison to some ILs reported in the literatures.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate, the T 0 values are lower than the value observed in 0.5 M LiTFSI in [N 2(2O2O1)3 ][TFSI] (210 K), 55 2.7 M LiFSI in [N 2(2O2O1)3 ][TFSI] (207 K), 55 or in 10 mol% LiFSI in [C 1O1mmor ][FSI] (202 K). 56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] This effect has been reported since the 2000s, and even in recent years, various literature have been published describing the development of new RTILs with ether functional groups and the analysis of their physicochemical properties. [9][10][11][12][13][14][15] Rauber et al reported that the development of RTILs composed of symmetric cation with ether group and symmetric anion. 14 Warrington et al investigated the introduction effect of ether group into piperidinium and morpholinium cations on their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…14 Warrington et al investigated the introduction effect of ether group into piperidinium and morpholinium cations on their physicochemical properties. 15 Understanding the structure-physicochemical properties correlation and properties as an electrolyte of ether-functionalized RTILs is quite important for the creation of the next generation of RTILs.…”
Section: Introductionmentioning
confidence: 99%